2018
DOI: 10.3390/children5030036
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Pediatric Complicated Pneumonia in an Ontario Local Health Integration Network

Abstract: Following the introduction of 7-valent pneumococcal vaccine (PCV7), while overall rates of invasive pneumococcal disease and pneumococcal pneumonia in children declined, rates of empyema increased. We examined changes in the incidence of hospitalization for pediatric complicated pneumonia (PCOMP) in Eastern Ontario, Canada, particularly since the introduction of the 13-valent vaccine (PCV13). A retrospective chart review was carried out evaluating previously healthy children admitted with PCOMP, which included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
0
9
0
1
Order By: Relevance
“…Initially, there was a pronounced decrease from about 16e18 (2010/11e2012/13) to 14 PPE/ PE per million children (2013/14 and 2014/15), which was followed by a re-increase to 17 and 15 cases per million in 2015/16 and 2016/ 17. Besides the use of pneumococcal vaccine, changes in PPE/PE incidence in populations with widespread pneumococcal vaccination may be associated with the use of more sensitive diagnostic methods, serotype replacement due to non-PCV serotypes, an increase in other PPE/PE-associated bacterial species, or the activity of the influenza season [7,17,20,30]. However, one of the lowest incidences of PPE/PE hospitalizations in our study was observed in the period 2014/15, which was an exceptionally strong influenza season in Germany [31].…”
Section: Discussionmentioning
confidence: 99%
“…Initially, there was a pronounced decrease from about 16e18 (2010/11e2012/13) to 14 PPE/ PE per million children (2013/14 and 2014/15), which was followed by a re-increase to 17 and 15 cases per million in 2015/16 and 2016/ 17. Besides the use of pneumococcal vaccine, changes in PPE/PE incidence in populations with widespread pneumococcal vaccination may be associated with the use of more sensitive diagnostic methods, serotype replacement due to non-PCV serotypes, an increase in other PPE/PE-associated bacterial species, or the activity of the influenza season [7,17,20,30]. However, one of the lowest incidences of PPE/PE hospitalizations in our study was observed in the period 2014/15, which was an exceptionally strong influenza season in Germany [31].…”
Section: Discussionmentioning
confidence: 99%
“…Another retrospective study in Eastern Ontario showed an increase of complicated pneumonia in post‐PCV13 period (2012–2015) in older children who were unlikely to receive PCV13 vaccination. However, when considering single complications, a rise in the incidence of NP was not found 31 . Only one study focused exclusively on the epidemiology of NP in childhood over the years.…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcus pneumonia yra dažniausias bakterinės pneumonijos sukėlėjas, todėl natūralu, kad daugelyje šalių įvestas visuotinis vaikų skiepijimas nuo pneumokokinės infekcijos reikšmingai sumažino sergamumą ir mirštamumą nuo šios ligos, ypač tarp vaikų iki penkerių metų. Nepaisant to, VĮVP ir jos sukeliamos komplikacijos tebėra aktuali problema visame pasaulyje [4,5]. Įvairių šaltinių duomenimis, komplikuotų pneumonijų dažnis mažai kinta, stinga jautrių ir specifiškų žymenų numatyti ligos eigai ir prognozei, etiologija nustatoma mažiau nei pusei susirgusiųjų VĮVP, o didėjantis mikrobų atsparumas vaistams lemia vis sudėtingesnį racionalaus ir savalaikio gydymo pasirinkimą [3].…”
Section: įVadasunclassified